Anticipating health innovations in 2030–2040: Where does responsibility lie for the publics?. (April 2018) - Lehoux, Pascale; Miller, Fiona A.; Grimard, Dominique; Gauthier, Philippe
Considering that public engagement is pivotal to the mission of Responsible Research and Innovation, this article's aim is to examine how members of the public conceive of the relationship between responsibility and prospective health technologies. We organized four face-to-face deliberative workshops and an online forum wherein participants were invited to comment on scenarios involving three fictional technologies in 2030 and 2040. Our analyses describe how participants anticipated these technologies' impacts and formulated two conditions for their use: they should (1) be embedded within professional care and services and (2) include social protection of individual freedom and privacy. By clarifying what technological direction shall be avoided and who shall act responsibly, these conditions emphasize our participants' understanding of society as much as their understanding of science. For new technologies to be deployed in socially responsible ways, public engagement methods should be developed alongside public governance and regulatory strategies.